Job Satisfaction among Registered Nurses Working in Public Hospitals: A Study in Windhoek, Namibia - Shalonda, Simon; Stellenberg, Ethelwynn; Amakali-Nauiseb, Taimi (New Ideas Concerning Arts and Social Studies Vol. 2, 2025)
Aims: The study examines and determines the level of job satisfaction among registered nurses in public hospitals in Windhoek, Namibia, focusing on hygienic and motivational factors as described by Herzberg's Two-factor Theory. Study Design: A quantitative exploratory descriptive design was applied to this study. Place and Duration of Study: This study was conducted in its natural setting, specifically at the only two public hospitals in Windhoek, Namibia. The study was conducted over a period of one month, October 2018. Methodology: The target population was the total population of registered nurses with more than one year of working experience. A pilot study was conducted to refine the methodology. A reliable, validated Minnesota questionnaire was used to collect the data. The researcher personally collected data. Data were analysed using SPSS and presented in the form of tables. Ethical approval was obtained from the Health Research Ethics Committee (HREC) reference # S18/03/046, the Ministry of Health and Social Services, and by way of informed consent from participants. Results: The level of job satisfaction differed among the participants; specifically, most participants were dissatisfied with their salaries (60%), working conditions (53%), and the chance for promotion and advancement opportunities (66%). Conclusion: Based on the findings of the study, there is an urgent need for policy interventions regarding promotion and advancement opportunities, improvement of the working conditions, and giving acknowledgement for the performance of nurses. This will enhance nurses' job satisfaction and retention in public hospitals.